Identifying Prospective Primary School Teachers' Ontologically Categorized Misconceptions on the Topic of "Force and Motion" - BAYRAM, HALE (Ekip Buro Makineleri A., 2019)
This research aims to reveal the misconceptions of prospective primary school teachers on the fundamental physics concepts such as force, frictional force, work, conservation of energy, mechanical energy, kinetic energy, potential energy, energy stored in springs on the topic of "Force and Motion" and to assess the misconceptions based on ontological view. In order to reveal the prospective primary school teachers' misconceptions, a two-tired "Concept Test on the Topic of Force and Motion" has been developed and used which consists of 17 items. The Cronbach's alpha value of the concept test was found to be 0.71. The study group of the research was 35 prospective primary school teachers at a foundation university (30 female and 5 male students) who were sophomore at primary school teacher education program. This research is characterized as a descriptive study. In the study, the misconceptions were assessed according to ontological categories, thus the reasons that lead these misconceptions were revealed based on ontology. Knowing the causes of misconceptions is very important for science education. Misconceptions can only be removed by planning and applying enough teaching methods focusing on causes of students' misconception. Therefore, identifying students' misconceptions based on ontological categories are very important because they facilitate revealing the causes of misconceptions. In the research, students' misconceptions related to the topic of force and motion were identified and discussed according to ontological categories. Analysis of concept test items revealed that the teacher candidates had 301 misconceptions that can be placed to upper categories, and 150 misconceptions that can be placed to the lateral categories and suggestions were provided based on the results of study. © 2019. All Rights Reserved.
Keywords: force and motion; misconception; Ontology